O feminino na rede: o corpo da/pela mulher no espaço digital - Paiva, Taís Iniz de (2017)
This present study has like a theme the discursive female body visible in the digital space of two feminists communities in the Facebook social network. From the French-Brazilian Discourse Analysis perspective, we analyze the corpus to verify, specifically, the violence against the female body. Starting, principally, with Michel Foucault's arche genealogical studies, we mobilize, in our analysis, the enunciative regularity, objectivation and subjectivation and dispositive concepts. We associate to these theoretical goal feminist studies of authors such as Judith Butler and Simone de Beauvoir. Our goal is to understand how a woman's body is said and done visible in these spaces and materials. Above all, we specify our look to the female body that suffer with physical violence because this is actually an important question in the woman’s social condition and must have an academic space to get visibility in language studies. The study also aims to contribute to the linguistic studies that take into account the effects of verbal about the imagery and vice versa, and the discursive Brazilian studies about the female gender. Our corpus of analysis consists of words and images clippings posted in communities such as Vadias Sampa and Não me Kahlo. In these clippings, we analyze the intra and interdiscursive relations, the speeches about the female body in digital spaces, which means, what has already been said and what is said about the female body. We analyze the already meanings constructed about the female body and how this is made actually in the digital communities. Our results indicate that the female body is still objectified like a subordinate body, but actually the digital spaces enables that the resistance’s speeches get visibility to resignify the female body, so became a strong and empowered body.